APPLICATIONS OF KINETOTHERAPY IN CONGENITAL HIP DISLOCATION - Danelciuc Francisc Tadeus (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The congenital hip dislocation is one of the serious limb malformations, which untreated on time determines functional sequelae with high degree of disability. Due to increased incidence, of the severe functional disability it causes and evolution to coxarthrosis, congenital hip dislocation represents a public health problem.